The Practice of MIN English Teachers through Teaching Learning Process and their Reflective Practice to Develop Professionalism - Najamuddin; Hery Rahmat (ELITE JOURNAL, 2019)
Teacher reflection has been part of continuous teachers’ development. Yet, in reality, only a few teachers conduct such self-reflection processes to improve their professional performance during the teaching learning process. This study aimed to know (1) the practice of MIN English teachers through teaching learning process; (2) the reflective practice of MIN teachers in order to improve their professionalism. This study belongs to qualitative descriptive as it describes data of the MIN teachers’ practice and their reflective practice through teaching learning process. The study result showed that (1) the MIN English teachers conducted teaching learning process by applying adequate three learning activities namely Introduction Activity, Main Activity, and Closing Activity along with the supported activities; (2) There are 3 types of reflective practice done by MIN English teachers through teaching learning process namely (a) the use of learning media; (b) the addition of exercise score; and (c) the changing of exercise content.